Impacts of climate change on drinking water quality in Norway. (28th February 2022) - Skaland, R. G.; Herrador, B. G.; Hisdal, H.; Hygen, H. O.; Hyllestad, S.; Lund, V.; White, R.; Wong, W. K.; Nygård, K.
Abstract: Climate change will lead to higher temperatures, increased precipitation and runoff, as well as more intense and frequent extreme weather events in Norway. More extreme rainfall and increased runoff are historically associated with higher concentrations of indicator bacteria, colour and turbidity in raw water of Norwegian waterworks. Regional information about the risk for drinking water deterioration by the end of the century is essential for evaluating potential treatment capacity upgrades at the waterworks. We combined locally downscaled future climate scenarios with historical associations between weather/runoff and water quality from a wide spread of waterworks in Norway. With continued climate change, we estimate higher concentrations of water quality indicators of raw water by the end of the century. The water quality is estimated to deteriorate mainly due to the projected increase in rainfall, and mainly in the Western and Northern parts of Norway. While large waterworks seem to be able to adapt to future conditions, the degradation of raw water quality may cause future challenges for the treatment processes at smaller waterworks. Combining these results with further studies of treatment effects and microbial risk assessments is needed to ensure sufficient treatment capacities of the raw water in the future. HIGHLIGHTS: Associations between weather/runoff and water at Norwegian waterworks were combined with local climate scenarios for the first time. Higher concentrations of water quality indicators of raw water in Norway in the future. The future increase in rainfall causes decreased raw water quality in the North and West of Norway. Decreasing raw water quality may cause challenges for the treatment processes of small waterworks